The Effectiveness of Self-Help Groups in Enhancing Self-Efficacy Among Patients with Gout Arthritis in the Sangihe Islands Community, Indonesia - Iswanto Gobel; Meistvin Welembuntu; Yanli Everson Tuwohingide; Rizza Lei Asuncion (Media of Health Research, 2026)
Community in island settings has limited access to healthcare facility as well as health information. Nevertheless, the strong kinship networks and social cohesion characteristic represent valuable sociocultural resources. This study aimed to evaluate the effectiveness of Self-Help Group (SHG) on self-efficacy among patients with gout arthritis living in the Sangihe Islands Regency, rural and remote archipelagic area located at the Indonesia-Philippines border.  A quasi-experimental design with pretest-posttest control group was conducted on September-November 2025, involving 134 participants (74 intervention, 60 control). Self-efficacy was measured using the validated and reliable Indonesian version of the Arthritis Self-Efficacy Scale-8 (ASES-8).  The intervention group received a single 45-60 minutes session (8 groups), Baseline groups were comparable in age, gender and employment, but differed in duration of illness and education level; both were controlled as covariates in analysis. The intervention group showed a significant increase in self-efficacy from pre-test (media=21.5) to post-test (median=68.5) (Wilcoxon test, p=0.001). Post-intervention self-efficacy was significantly higher in the intervention group (mean=67.61; median 68.5) compared to the control group (mean=41.18; median 39) (Mann-Whitney test, p=0.001). After adjusting for duration of illness and education level, the intervention effect remained highly significant (ANCOVA, F=173.56; p<0.001), with no significant covariate or interaction effects. These findings emphasize The SHG Method can increase self-efficacy among patients with gout arthritis. This low-cost, community-based method is recommended for integration into routine health education at community health centers to enhance chronic disease self-management in island and remote settings.Community in island settings has limited access to healthcare facility as well as health information. Nevertheless, the strong kinship networks and social cohesion characteristic represent valuable sociocultural resources. This study aimed to evaluate the effectiveness of Self-Help Group (SHG) on self-efficacy among patients with gout arthritis living in the Sangihe Islands Regency, rural and remote archipelagic area located at the Indonesia-Philippines border.  A quasi-experimental design with pretest-posttest control group was conducted on September-November 2025, involving 134 participants (74 intervention, 60 control). Self-efficacy was measured using the validated and reliable Indonesian version of the Arthritis Self-Efficacy Scale-8 (ASES-8).  The intervention group received a single 45-60 minutes session (8 groups), Baseline groups were comparable in age, gender and employment, but differed in duration of illness and education level; both were controlled as covariates in analysis. The intervention group showed a significant increase in self-efficacy from pre-test (media=21.5) to post-test (median=68.5) (Wilcoxon test, p=0.001). Post-intervention self-efficacy was significantly higher in the intervention group (mean=67.61; median 68.5) compared to the control group (mean=41.18; median 39) (Mann-Whitney test, p=0.001). After adjusting for duration of illness and education level, the intervention effect remained highly significant (ANCOVA, F=173.56; p<0.001), with no significant covariate or interaction effects. These findings emphasize The SHG Method can increase self-efficacy among patients with gout arthritis. This low-cost, community-based method is recommended for integration into routine health education at community health centers to enhance chronic disease self-management in island and remote settings.